Enhancing Productivity and Welfare: The Impact of Farmer-Cooperative Partnerships in the Oil Palm Sector - Yosua, Relansius; Susilo, Achmadi; Wisnujati, Nugrahini Susantinah (PT. Sangadji Media Publishing, 2024)
This study investigates how palm oil farmers can enhance their productivity and welfare through strategic partnerships with cooperatives, with a focus on the Sinar Berkah Cooperative. Using a quantitative approach and employing structural equation modeling (SEM), the research examines the influence of cooperative membership, access to resources, education and training, and government support on farmers’ productivity. Data was collected from both primary and secondary sources, with respondents purposefully selected from the largest farmer groups within the cooperative. Key findings highlight the significant role of resource access—such as capital, raw materials, and technology—in driving productivity improvements. The study also underscores the cooperative’s critical role in facilitating legal recognition and improving market access, helping farmers overcome business challenges. However, it reveals that current education and training initiatives, along with government support, have not yet yielded significant improvements in productivity. These findings suggest that more targeted interventions are required to fully realize the potential benefits of such partnerships. The SEM analysis provides insights into the key factors influencing the productivity and welfare of oil palm farmers, offering valuable recommendations for enhancing business outcomes through more efficient and supportive cooperative-farmer collaborations.